Conversion of CO2 into renewable fuel over Pt–g-C3N4/KNbO3 composite photocatalyst. Issue 113 (2nd November 2015) - Shi, Haifeng; Zhang, Chengliang; Zhou, Changping; Chen, Guoqing
Abstract : g-C3 N4 /KNbO3 composite photocatalyst was prepared and developed for reduction of CO2 into CH4 . Abstract : g-C3 N4 /KNbO3 composites were fabricated by ultrasonic dispersion followed by heat treatment method, and developed as visible-light-sensitive photocatalysts for CO2 conversion. The photocatalysts were characterized by X-ray powder diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, photoluminescence spectra, nitrogen adsorption–desorption, and UV-vis diffuse reflection spectroscopy. HRTEM revealed that an intimate interface between g-C3 N4 and KNbO3 was formed in the g-C3 N4 /KNbO3 composite. The g-C3 N4 /KNbO3 composite exhibited superior photocatalytic performance for CO2 reduction compared to g-C3 N4 under visible-light illumination. Such a significant enhancement in the photocatalytic activity was mainly ascribed to the improved separation efficiency of photoinduced carriers at the interface of the g-C3 N4 /KNbO3 composite, which was beneficial for separating the photoinduced electron–holes and thus improving the photocatalytic performance. The present study would provide a useful method to develop an effective composite photocatalyst for CO2 reduction under visible light irradiation.